CNM Audios: A Psychoanalytical Approach - Fodale Vargas, Luis Ernesto (2019)
This study presents a qualitative research based on the psychoanalytic theoretical framework with the purpose of realize an analysis of the 101 audios published by the IDL Reporteros website, about corruption in the Consejo Nacional de la Magistratura of Perú. The psychoanalytic framework allows to analyze the presence of unconscious mechanisms inscribed in the instituted links between the main characters of these audios, also called «hermanitos». The research presents a route of the psychoanalytic ideas related to group and institution phenomena, from Sigmund Freud to contemporary authors like Kaës and Ulloa. Freud’s work allows to analyze unconscious mechanisms like projection, idealization and identification. Kaës proposes group mechanisms like denied pact and narcissistic contract, and Ulloa highlights the tragic entrapment, an institutional and social device that perpetuates cruelty where there’s no other that intercede. The results show the emergence of eight categories obtained through thematic analysis. Based on the results, we describe the functioning of the power structure of the hermanito’s group, maintained on corruption and an excessive seizure desire and exploitation of others, characteristic of omnipotent fantasies expressed on denied pacts or agreements that pretend to be above civilization and its discontents. About its functioning, we can remark a common language and speaking in code that brings cohesion to the group and allows observing the relationship between subjects. The group reflects a vertical power structure in which subordinates are exploited and forced, as well as dependents. In it stand outs unconscious alliances with evident family springs that ensure its continuity by activities of enjoyment and exclusivity. Likewise, external threats generate paranoid fantasies that reinforce speaking in code, as well as place out a persecutor that threats the perpetration of this structure.